Relative Controllability of Nonlinear Neutral Fractional Volterra Integrodifferential Systems with Multiple Delays in Control - Balachandran, K.; Divya, S. (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we investigate the global relative controllability of nonlinear neutral fractional Volterra integrodifferential systems with multiple delays. Controllability criteria for nonlinear fractional order systems are established. The results are obtained by using the Schauder fixed point theorem. Moreover, some numerical examples are provided to illustrate the effectiveness and applicability of the proposed criteria.